The big book of reproducible graphic organizers : 50 great templates to help kids get more out of reading, writing, social studies, & more - Jacobson, Jennifer, 1958-; Raymer, Dottie, 1955- (Scholastic Professional Books, 1999)
"A collection of visual representations that provide students with successful methods of organizing, interpreting, and understanding material in Language Arts, Geography, History, Science, Mathematics, and study skills."